(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The formation of new blood vessels that transport oxygen and nutrients is the basis of most physiological and pathological processes. However, microangiogenesis is one of the stages of tumor growth and subsequent tumor spread, progression and metastasis. Various proangiogenic and antiangiogenic factors play a role in the regulation of neoangiogenesis. Methods and materials. Effect of therapy is assessed with ultrosound examination, CT, tonometry, ECG, ExoKG and MRI. 50 patients have operated and effect is assessed with hystologycal examination as well. Summary. We believe that as the usage of VSP inhibitors increases, treatment-induced hypertension resulting from earlier tumor diagnosis and longer medication duration will become more common. During a patient’s follow-up, we advise oncologists to be aware of this possibility and make sure that blood pressure is closely checked.